Students' Awareness on Information Security between Own Perception and Reality – An Empirical Study - Victoria Stanciu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The accounting profession is evolving aiming at responding in an adequate manner to the society's requirements dominated by the IT insertion in all the aspects of the life. The IT knowledge and skills needed by the accounting professionals are increased and the accounting faculties are determined to respond to the new professional requirements. This paper discusses the accounting students' awareness in regard with information security. The research performed emphasized the significant gap between the students' perception on their information security awareness and the reality. The study revealed that the students' computing knowledge is more technical and less addressed to information security issues. The research conclusions emphasize the urgent need for improving the universities' curriculum in regard with information security issues and students' training using information security awareness programs. The Romanian literature is scarce in regard with this topic. From this perspective, the present paper signals the need to deepen the students' training process aiming at better preparing the students for the professional life and make them be more employable.
Keywords: A2; M41; M15; 650; IT Security; University Education; Employment Skills; IT Risk Awareness